Variation in the condition-dependence of individual sexual traits in male eastern mosquitofish, Gambusia holbrooki. (14th February 2019) - Fox, Rebecca J; Gearing, Ellen E; Jennions, Michael D; Head, Megan L
Abstract: Most sexually selected traits are costly to produce and therefore tend to show condition-dependent expression. But individuals have a finite set of resources to invest across the multiple traits on which sexual selection acts. This necessarily leads to trade-offs among individual traits and between different reproductive stages. The effect of male condition on trait expression might therefore vary for different sexually selected traits depending on the marginal gains from investment into one trait rather than another. We manipulated the diet of eastern mosquitofish (Gambusia holbrooki) to test the condition-dependence of 4 components of male mating effort that are under precopulatory sexual selection (male–male aggressiveness, time spent with females, rate of copulation attempts, and male mate choice). We found positive condition-dependence of both the time spent with females and the rate of copulation attempts, but negative condition-dependence of male aggression towards rivals (all P < 0.05). By contrast, the level of male mating preference for larger, more fecund females did not vary significantly with male condition. Our results highlight the importance of incorporating variation in resource acquisition, hence condition, into allocation models that predict investment into multiple sexually selected traits. Abstract : Males have limited resources to invest in the many traits that affect their mating success. So should males that vary in the resources at their disposal have different allocation strategies? For example, should males in poor condition increase their aggression towards rivals or their investment in mating attempts? By experimentally manipulating diets, we showed that male mosquitofish in low condition are more aggressive towards rivals, and no less choosy about mates, and spent less time attempting to copulate than males in high condition.